Policy analysis as "text" in higher education: Challenging South Africa's "use of official languages act": A case-based approach - Ralarala, M.K. (South African Journal of Higher Education, 2019)
The literature on policy science demonstrates that deeper insight into the complexities surrounding notions of the policy process, and of policy formulation and policy-making, can be drawn from policy analysis. As such, some scholars who have taken note of this fact have paid serious attention to policy analysis. As a starting point in this paper, I deliberate on the assorted definitions of policy offered by various scholars in the field of policy science. Furthermore, the paper engages with the notion of policy analysis from the perspective of policy text. Regarding the methodological position, this paper makes use of a case study in respect of the Use of Official Languages Act 12 of 2012, with specific reference to the South African Qualification Authority’s language policy development and formulation process as a unit of analysis. From a conceptual and analytical perspective, the paper draws on the notion of presupposition as a viable tool for analysing policy text. Finally, in this paper I propose a textual cycle which could account for stages of policy text/word development, and thus, an account of pertinent research questions is provided.